Analysis of Actors in Promoting Recognition of Indigenous Peoples Policy Post Constitution Court Rulling No.35 (Study on AMAN’s and the Network’s Role in Promoting the Recognition of Indigenous Peoples Through Village Law and Recognition and Protection of - Arsyad, Idham; Sunito, Satyawan; Kartodiharjo, Haryadi (Sodality: Jurnal Sosiologi Pedesaan, 2016)
ABSTRACTThe judicial review allegation conducted by the Nusantara Indigenous Peoples Alliance (AMAN) against Act No. 41/1999 on Forestry has resulted Constitutional Court Rulling No.35 (Putusan MK 35) which sucessfully excluded indigenous forests from the state forest. This ruling has implications for the process of new policy formulation related to the recognition and protection of indigenous people and their customary land. Therefore this study aims to look at the influence of the Putusan MK 35 on the formulation of the Village Law and Recognition and Protection of Indegenous People Bill (RUU PPMHA)through the role of actors and discourses. This study found that; The Putusan MK 35 affect the substance of the Village Law with the inclusion of the indegenous village nomenclature within the law. A common discourse and political interests among actors made the Village Law formed quickly. However the rulling did not succeed in promoting PPMHA Law given the conflict of the actors was very high and the discourse about social unit of indegenous people was unclear at that timeKeywords: indigenous peoples, indigenous forest, indigenous village, recognition and protection, costumary landABSTRAKGugatan judicial review yang dilakukan oleh Aliansi Masyarakat Adat Nusantara (AMAN) terhadap UU No.41 tahun 1999 tentang Kehutanan yang menghasilkan Putusan Mahkamah Konstitusi No.35 (Putusan MK 35) yang mengeluarkan hutan adat dari hutan negara. Kebijakan ini berimplikasi pada proses pembentukan kebijakan baru terkait dengan pengakuan dan perlindungan masyarakat adat dan wilayah adatnya. Karenanya, penelitian ini bertujuan untuk melihat pengaruh Putusan MK 35 terhadap Undang-Undang tentang Desa dan Rancangan Undang-Undang tentang Pengakuan dan Perlindungan Masyarakat Hukum Adat (RUU PPMHA) melalui analisis aktor dan diskursus yang berkembang. Penelitian menemukan bahwa Putusan MK 35 mempengaruhi subtansi Undang- Undang Desa dengan masuknya nomenklatur desa adat dalam undang-undang. Diskursus dan kepentingan yang saya sama dari aktor membuat undang-undang ini terbentuk secara cepat. Namun tidak berhasil dalam RUU PPMHA karena konflik para aktor sangat tinggi dan diskursus mengenai unit sosial masyarakat hukum adat tidak jelas.Kata kunci: masyarakat adat, hutan adat, desa adat, pengakuan dan perlindungan, wilayah adat.